Wednesday

April 23, 2014

April 23, 2014

Posted by **abdo** on Wednesday, April 18, 2007 at 11:02pm.

(cosx / 1-sinx ) = ( 1+sinx / cosx )

I recall this question causing all kinds of problems when I was still teaching.

it requires a little "trick"

L.S.

=cosx/(1-sinx) multiply top and bottom by 1+sinx, (creating the difference of square pattern)

=cosx(1+sinx)/[(1-sinx)(1+sinx)]

=cosx(1+sinx)/(1-sin^2x)

=cosx(1+sinx)/cos^2x divide by cosx

= (1+sinx)/cosx

= R.S.

Wow !!

**Related Questions**

Pre-Calc - Trigonometric Identities Prove: (tanx + secx -1)/(tanx - secx + 1)= ...

Pre-calc - prove the identity: (cosx)(tanx + sinx cotx)=sinx+cos(squared)x i ...

Trigonometry Check - Simplify #3: [cosx-sin(90-x)sinx]/[cosx-cos(180-x)tanx] = [...

Math - Pre- Clac - Prove that each of these equations is an identity. A) (1 + ...

Mathematics - Trigonometric Identities - Prove: (tanx)(sinx) / (tanx) + (sinx...

Math - Verify the identity . (cscX-cotX)^2=1-cosX/1+cosX _______ sorry i cant ...

trigonometry - can i use factoring to simplify this trig identity? the problem ...

Trigonometry - Prove the following trigonometric identities. please give a ...

Trigonometry. - ( tanx/1-cotx )+ (cotx/1-tanx)= (1+secxcscx) Good one! ...

Mathematics - Trigonometric Identities - Prove: sinx + tanx = tanx (1 + cosx) ...